2000
DOI: 10.4049/jimmunol.164.8.3996
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirements for C-C Chemokine and IL-2 Production by Naive, Previously Activated, and Anergic T Cells

Abstract: Ag presented by activated APCs promote immunogenic responses whereas Ag presented by resting APCs leads to tolerance. In such a model, the regulation of cytokine release by the presence or absence of costimulation might potentially play a critical role in dictating the ultimate outcome of Ag recognition. C-C chemokines are a structurally defined family of chemoattractants that have diverse effects on inflammation. We were interested in determining the activation requirements for chemokine production by CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…TSP1 signaling via CD47 inhibits TCR signaling, including induction of the early activation marker CD69 (28, 33, 42). Consistent with the previous report that VEGF inhibits T cell activation (19), VEGF treatment resulted in a 4-fold reduction in CD69 mRNA expression induced by activation of WT Jurkat T cells in the presence of anti-CD3+CD28 for 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TSP1 signaling via CD47 inhibits TCR signaling, including induction of the early activation marker CD69 (28, 33, 42). Consistent with the previous report that VEGF inhibits T cell activation (19), VEGF treatment resulted in a 4-fold reduction in CD69 mRNA expression induced by activation of WT Jurkat T cells in the presence of anti-CD3+CD28 for 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of tumor-derived CCL3 and CCL4 in antitumor immunity has not been well delineated, a recent report concerning CCL3 may warrant further investigation. Lerner et al [90] reported that CCL3 was secreted by T cells stimulated with signal one in the absence of signal two and accordingly may play a role in T cell tolerance. As a result, it is interesting to speculate that tumor-derived CCL3 may play a role in tumor-induced immune tolerance.…”
Section: Ccl3 and Ccl4mentioning
confidence: 98%
“…The benefit of monoclonal antibodies (mabs) against surface receptors for separating those leucocyte subpopulations was shown earlier using panning techniques [20] or immunomagnetic separation [22]. In the present study sIgM leucocytes (sIgM T lymphocytes, NK cells and thrombocytes) depleted from sIgM + B lymphocytes using two mabs against trout IgM were used to characterise growth factors which were secreted by sIgM leucocytes after mitogenic stimulation into culture supernatants (conditioned media, CM), a well known phenomena of activated mammalian T lymphocytes [29,30]. For an optimal detection of secreted molecules in PAGE and Westernblot a serum-free cultivation systems was used.…”
Section: Discussionmentioning
confidence: 99%